Bioreactors, gas delivery systems and supporting technologies for microbial synthesis gas conversion process. (September 2019) - Yasin, Muhammad; Jang, Nulee; Lee, Mungyu; Kang, Hyunsoo; Aslam, Muhammad; Bazmi, Aqeel Ahmed; Chang, In Seop
Abstract: Bioprocessing of synthesis gas (syngas) and waste gases from industrial streams has been developed as a potential option to produce biofuels and biochemicals. However, poor solubility and mass exchange of syngas, low cell biomass, and productivities are key bottlenecks for technology commercialization. All aforementioned hurdles are mainly the outcome of poor gas-liquid mass transfer (GLMT). Efforts have been devoted by employing different reactor configurations, improving gas delivery systems, and altering properties of the system. To date, all available options have not been critically reviewed and an optimal solution to get high GLMT is lacking to drive technology towards practicality and economic feasibility. Hence, aim of this article is to compare different options to increase GLMT in syngas fermentation. Comprehensive discussions are made on state of the art reactor configurations, gas delivery devices and supporting technologies. Finally, a reactor system for high GLMT, high cell concentration and productivity is proposed. Graphical abstract: Unlabelled Image Highlights: Bioreactors and gas delivery devices for syngas fermentation are compared. Supporting technologies to further increase mass transfer are introduced. Optimized gas fermentation system for high mass transfer is proposed.